Happiness Index and Performance a Psychological Perspective: Exploring the Link Between Happiness, Performance, and Social Change (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Today, the world is in great turmoil. Not only do we seewar and destruction, but also witness growing poverty and hunger, the emergenceof new slavery, and the ravaging of our ecosystem. Some have defined the modernworld not in terms of technological advances but in terms of the growing gapbetween “haves” and “have notes.” This division of the world’s population isnot simply economic but also social and political i.e., a separation of worldpopulations between those with basic human rights and those without it. Infact, it is probably more accurate to describe today’s world not as a divisionbetween “haves” and “have not” but rather between “haves” and “disposablepeople.” Today’s “disposable people” are those who toil for pennies a day insweatshops for global corporations, those who are kidnapped and trafficked inmodern-day slavery and those without access to basic necessities such as freshdrinking water. Ideas for social change come from individuals – or, moreaccurately, they come from individuals through discussions with others.Individuals can turn ideas into action, but truly effective action emerges fromcollective efforts involving large numbers of people at the grass root level.In other words, social change hinges on the ability of individual activists toorganize with others collectively. This requires not only the reaching ofcommon goals and a common understanding of issues but also grasping theimportance of forging new human relationships based on mutual respect andsolidarity.